Survival analysis of 219 dogs with hyperadrenocorticism attending primary care practice in England. (21st March 2020) - Schofield, Imogen; Brodbelt, David C; Wilson, Anna R L; Niessen, Stijn; Church, David; O'Neill, Dan
Abstract : Background: Hyperadrenocorticism is an endocrine disease routinely encountered within primary care practice; however, few studies evaluating survival beyond diagnosis have studied this population. Methods: This retrospective cohort study analysed the electronic patient records of 219 cases of hyperadrenocorticism from a sample of dogs attending primary care practices in England. Kaplan‐Meier plots examined the cumulative survival and Cox proportional hazard regression modelling identified factors associated with the hazard of all‐cause mortality. Results: In the analysis, 179/219 (81.7 per cent) hyperadrenocorticism cases died during the study period with a median survival time from first diagnosis of 510 days (95% CI 412 to 618 days). Trilostane was used in 94.1 per cent of cases and differentiation between pituitary‐dependent and adrenal‐dependent disease was made in 20.1 per cent of cases. In the multivariable analysis, dogs weighing greater than or equal to 15 kg (HR 1.51, 95% CI 1.06 to 2.15, P=0.023) and those diagnosed greater than or equal to 13 years of age (HR 3.74, 95% CI 2.29 to 6.09, P<0.001) had increased hazards of all‐cause mortality. Dogs that had their initial trilostane dose increased had a favourable prognosis (HR 0.49, 95% CI 0.32 to 0.76, P=0.015). Conclusion: This study shows that survival from diagnosis of hyperadrenocorticism appears fair for many dogs and provides primary care practitioners with relatable benchmark prognostic figures.